2022
DOI: 10.3390/nano12193316
|View full text |Cite
|
Sign up to set email alerts
|

Tug-of-War Driven by the Structure of Carboxylic Acids: Tuning the Size, Morphology, and Photocatalytic Activity of α-Ag2WO4

Abstract: Size and morphology control during the synthesis of materials requires a molecular-level understanding of how the addition of surface ligands regulates nucleation and growth. In this work, this control is achieved by using three carboxylic acids (tartaric, benzoic, and citric) during sonochemical syntheses. The presence of carboxylic acids affects the kinetics of the nucleation process, alters the growth rate, and governs the size and morphology. Samples synthesized with citric acid revealed excellent photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Figure d shows the results of scavenger tests performed for the CeO 2 NCs used to unveil the RhB photodegradation process. To investigate its mechanism selective scavengers of different reactive species e – (silver nitrate), h + (ammonium oxalate), ·OH ( tert -butyl alcohol), and ·O 2 – ( p -benzoquinone) were added to the RhB solutions. While no significant changes were observed on the samples synthesized in ethanol since their photocatalytic efficiency is very close to actual photolysis, on the sample synthesized in acetone, a reduction for all scavengers can be observed, especially the ·O 2 – radical. Hence, we know that, in the degradation process, all reactive species participate in breaking down the RhB molecule, and there is a greater contribution of ·O 2 – radicals.…”
Section: Resultsmentioning
confidence: 89%
“…Figure d shows the results of scavenger tests performed for the CeO 2 NCs used to unveil the RhB photodegradation process. To investigate its mechanism selective scavengers of different reactive species e – (silver nitrate), h + (ammonium oxalate), ·OH ( tert -butyl alcohol), and ·O 2 – ( p -benzoquinone) were added to the RhB solutions. While no significant changes were observed on the samples synthesized in ethanol since their photocatalytic efficiency is very close to actual photolysis, on the sample synthesized in acetone, a reduction for all scavengers can be observed, especially the ·O 2 – radical. Hence, we know that, in the degradation process, all reactive species participate in breaking down the RhB molecule, and there is a greater contribution of ·O 2 – radicals.…”
Section: Resultsmentioning
confidence: 89%
“…As a result, the high binding energy peak at 532.07 eV and the low binding energy peak at 530.19 eV in the O 1s spectrum can be attributed to oxygen atoms bound to the crystalline lattice (O L ) and oxygen atoms not bound to the lattice, respectively. 29 The O 1s peak at 532.07 eV includes oxygen species such as W-O, Ag-O, V-O, and O-OH, with the latter representing adsorbed oxygens from water (O W ), while the 530.19 eV O 1s peak corresponds to W-O-W bonding in OL. The O 1s peak in the 532.07 eV region may also include the contribution of superficial oxygen vacancies (V O ), as it is believed that the binding energy of O 1s resulting from this bond is similar to that of other oxygen atoms not bound to the lattice.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Our research group has previously reported how different solvents and surfactants in the reaction medium directly impact the final morphology of the synthesized AW microcrystals. 2,29,30 Specifically, doping processes using Zn 2+ and Ni 2+ metals have been found to alter the morphology of the synthesized AW samples, thereby affecting the number of active sites on the surface and conse- † Electronic supplementary information (ESI) available. See DOI: https://doi.org/ 10.1039/d3dt02352d a CDMF-UFSCar, Universidade Federal de São Carlos, P.O.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the sonochemical method was employed to achieve the control size and morphology of the a-Ag 2 WO 4 materials by using three carboxylic acids (tartaric, benzoic, and citric). The degradation process of Rhodamine B (RhB) dye was excellent, reaching 100% degradation in 60 min for the as-synthetized samples with citric acid, which have nanoscale dimensions [95].…”
Section: Synthesis Of the Different Polymorphs Of Ag 2 Wo 4 -Based Ma...mentioning
confidence: 99%